The Evaluation of Career Indecision in Career Development - Lewko, John H. (Canadian Journal of Counselling and Psychotherapy, 2007)
The current state of research on career indecision is examined through a review of two bodies of literature: (a) variables that have been consistently investigated as predictors of career indecision, and (b) tools incorporated to measure career indecision. The literature provides no strong basis for identifying factors that shape an individual's degree of "undecidedness" nor is it sufficient to warrant the continued practice of accepting sub-groups of "decidedness" as conceptually meaningful. Given the current state of research, the ability to evaluate career development by focusing on career indecision is limited. Eight issues are raised that would impact on evaluation efforts in this area. Practitioners are encouraged to test the validity of their own mental models that underlie their use of career indecision in intervention strategies.